Uncovering the Kingdom of Heaven: Archaeological Exploration and the Gospel of Matthew - Kitchen, Merrill (Buried History: The Journal of the Australian Institute of Archaeology, 2011)
The ‘Kingdom of God’ is a common term found in the New Testament Gospels as a descriptor of the reign of God, but the Gospel of Matthew uniquely and consistently replaces this term with the ‘Kingdom of Heaven.’ Interestingly, the mosaic art uncovered in a number of second to fifth century CE synagogues excavated over the last sixty years in Israel-Palestine also portray the heavens symbolically using the form of zodiacs and surrounding them with symbols of Israel’s ancient story. In particular, the story board of the mosaic floor of an excavated fifth-century CE synagogue in Zippori (Sepphoris) shows remarkable similarities with a narrative structure discernible within the Gospel of Matthew. This may point to a period of common cultural understanding, and even dialogue, between Rabbinic Judaism and Early Christianity.